29Si and 27Al MAS NMR spectroscopic studies of activated metakaolin-slag mixtures. (7th March 2022) - Souayfan, Faten; Rozière, Emmanuel; Paris, Michaël; Deneele, Dimitri; Loukili, Ahmed; Justino, Christophe
Highlights: Activated metakaolin and metakaolin-slag mixtures studied at high H2 O/Na2 O ratios. Different approaches of Si and Al NMR spectra analysis are compared. Formation of a heterogeneous phase involved in the transformation of 3D geopolymer network to C-A-S-H. Higher reactivity of metakaolin detected in slag-metakaolin mixtures. Abstract: Blending metakaolin with slag in alkali-activated materials represents a promising way to achieve both acceptable engineering properties and durability. Nuclear Magnetic Resonance (NMR) spectroscopy has appeared as a key technique to investigate the structure of alkali-activation products. However, there is not a consensus on the analysis of NMR spectra to identify the phases formed in binary slag-metakaolin mixtures. This paper characterizes the phase composition and the reaction degree of alkali-activated metakaolin-slag blends, with special emphasis on the effect of H2 O/Na2 O ratio. Different approaches based on the literature are presented and implemented to analyze NMR data. The results suggest the formation of a heterogeneous phase involved in the transformation of 3D network to C-A-S-H. The evaluation of the reaction degree showed that the incorporation of slag in activated metakaolin mixtures resulted in higher reactivity of metakaolin and higher compressive strength.